RETHINKING THE THOUGHT OF JAMALUDDIN AL-AFGHANI: INTELLECTUAL LEGACY FOR ISLAMIC REFORM IN THE MODERN MUSLIM WORLD - Nagib Romadhony; Masbuang; Sholahuddin Al Ayubi; Andi Rosa (Adisam Publisher, 2025)
This study aims to analyze the relevance of Jamaluddin al-Afghani’s rationalist and Pan-Islamist thought in addressing the challenges of Islamic reform in the modern Muslim world. The background of the research is rooted in the need for Muslims to overcome intellectual stagnation, colonial subjugation, and geopolitical fragmentation through a rational and inclusive paradigm. This research employs a qualitative approach using library research methods, with descriptive-interpretative analysis of al-Afghani’s works and related secondary literature. The findings reveal that al-Afghani placed rationality at the core of theological and socio-political reform, rejecting blind imitation (taqlid) and fatalism, while emphasizing ijtihad and education. His Pan-Islamist ideas served as a strategic foundation for the global revival of the Muslim ummah, transcending ethnic and national boundaries. His thought inspired later reformers such as Muhammad Abduh and Rashid Rida in shaping a modern, critical, and progressive Islam. Al-Afghani’s intellectual legacy remains highly relevant in confronting contemporary issues such as extremism, authoritarianism, and identity crises within the Muslim world.